VEGFR-2 receptor – target for anticancer therapy - Hucz, Joanna; Szala, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2006)
Vascular endothelial growth factor (VEGF) is a potent mitogen that plays a key role in the growth and maintenance of vascular endothelial cells as well as in the development of new physiological and tumour blood vessels. Among cell surface receptors responsible for internalizing this growth factor is VEGFR-2, a member of the receptor type tyrosine kinase superfamily. Following VEGF-mediated activation of this receptor in tumour endothelial cells, a series of biochemical events is initiated, leading to division of these cells and, subsequently, to the formation of new tumour blood vessels. This review presents molecular strategies of targeting the VEGFR-2 receptor for therapeutic purposes. Some of these strategies have been attaining preclinical or clinical stage of development, e.g. anti-VEGFR-2 antibodies, cyclic peptides, two-domain peptides, low-molecular-weight tyrosine kinase inhibitors or antisense oligonucleotides blocking VEGFR-2 expression. Attempts have also been made to take advantage of the immune response directed against blood vessels exhibiting this receptor.